Politically Correct Terms In The Jakarta Post - Muhammad Anwar; A.K Amarullah; Yuni Utami Asih (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2023)
The purpose of this study was to find out the types of political correctness used in The Jakarta Post’s news website. The design of the study was qualitative approach. The sample of this study was eleven news articles taken from March to May 2021. Political correctness categorizations were taken from the works of John (2017), Andary-Brophy (2015), and Monashnenko, Amelina, and Shynkaruk (2021). The finding was that The Jakarta Post used: eight PC-Liberalism and three PC-Authoritarianism types; two politeness, one accuracy, three academic, and five conformity variants; and seven euphemisms of discrimination, one euphemism of unpleasant reality, and three euphemisms of people’s lives. The data analysis result exhibited that The Jakarta Post mainly used political correctness for conformity, adhering to the practices of liberalism, and avoiding terms that may be discriminatory. The goal of the study was to provide a better understanding and description of political correctness as well as a model for English language education department students to do further comparable research.